The Geostrategic Dynamics of the China-Djibouti Partnership - Ladan, Dalmar (Department of Political Science - Universitas Sains Al-Qur’an, 2024)
This article examines the implications of evolving threats on China's foreign policy, particularly through its strategic partnership with Djibouti in Africa. This partnership is perceived as a mechanism for achieving foreign policy objectives through cooperative interdependence. Utilizing secondary data obtained from official documents on the Ministry of Foreign Affairs websites of both the People's Republic of China and the Republic of Djibouti, along with online data, this study employs qualitative methods grounded in the concept of strategic partnership and geostrategy theory. As a tool of foreign policy, strategic partnerships enable China to navigate global dynamics and fulfill its international interests. The findings suggest that the partnership with Djibouti represents an initial possible step towards enhancing Africa's global integration with China.